2023
DOI: 10.1101/2023.11.01.565227
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Reconciling the spectrum of RORγt+antigen-presenting cells

Tyler Park,
Christina Leslie,
Alexander Y. Rudensky
et al.

Abstract: Three recent contemporaneously published papers1–3showed that antigen-presenting cells (APC) expressing the nuclear receptor RORγt instruct peripheral regulatory T (pTreg) cell differentiation and establish tolerance to the gut microbiota. These studies identified a spectrum of RORγt+APCs, distinct from dendritic cells, that included type 3 innate lymphoid cells (ILC3s) as well as novel APC types. Given the discordant conclusions as to the nature of the pTreg-inducing APC and the divergent nomenclature used in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 7 publications
2
6
0
Order By: Relevance
“…Of note, TCII showed highest expression of RORψt + DC signature genes, while TCIV showed lowest expression of these genes (Fig 6a). In line with previous analyses ( 34 , 40 ), TCIII and TCIV showed high expression of the eTAC gene Tnrfsf11a , although Aire expression was only observed in TCI and TCII (Fig. S9c).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Of note, TCII showed highest expression of RORψt + DC signature genes, while TCIV showed lowest expression of these genes (Fig 6a). In line with previous analyses ( 34 , 40 ), TCIII and TCIV showed high expression of the eTAC gene Tnrfsf11a , although Aire expression was only observed in TCI and TCII (Fig. S9c).…”
Section: Resultssupporting
confidence: 91%
“…Thetis cells have been described in neonatal mLN and strongly resemble Janus cells although they are apparently absent from skin draining LN ( 34 ). Despite their transcriptional similarities to Janus cells, only a fraction of Thetis cells (TCI and TC III) express AIRE, while TCIV expresses ITGβ8 but lacks AIRE ( 34 ) and it is unclear if Thetis cells even exist in adult mice ( 40 ). While Janus and Thetis cells in mice have been shown to drive T cell tolerance, R-DC-like cells that resemble Thetis cells have been described in human tonsil, where they can activate T cells ( 41 ).…”
Section: Introductionmentioning
confidence: 99%
“…Given that TCs were enriched in fetal vs adult lymph node samples in the Human Gut Atlas, 14 RORγt + APCs, may in part be due to studies utilizing the Aire-GFP BAC transgenic ('Adig') mouse 39 to identify and characterize RORγt + Aire + cells. We and others have shown that Aire-GFP expression is not synonymous with Aire protein expression, 37,47 suggesting over-reporting of peripheral Aire expression. Indeed Aire-GFP expression was found in ~50% of ILC3s which do not express Aire protein and are not considered to be part of the spectrum of RORγt + eTACs.…”
Section: The Tis Cell S Are Con S Erved Across S Pecie Smentioning
confidence: 70%
“…Our post-hoc analysis of three published datasets alongside our own data resolved the full spectrum of RORγt + APCs, demonstrating transcriptional overlap between all cell types identified across the four studies. 37 In each dataset, RORγt + APCs encompassed ILC3s, distinguished by the expression of canonical ILC3 markers RORα and CXCR6, as well as non-ILC3 cells that mapped to the 4 Thetis cell subsets. Aire-expressing JC1 33 and RORγt + eTAC I 32 were found to be synonymous with Aire + TC I whereas JC2 33 and RORγt + eTAC II 32 encompassed a heterogenous mix of cells spanning TC II, III, and IV cells.…”
Section: The Full S Pec Trum Of Rorγ T + Ap C S-b E Yond E X Tr A-thy...mentioning
confidence: 99%
See 1 more Smart Citation